Optimised and dynamic KYC system based on blockchain technology. (20th August 2019) - Parra-Moyano, José; Thoroddsen, Tryggvi; Ross, Omri
Systems that use blockchain technology to improve the know-your-customer (KYC) process have only been proposed at a conceptual level and all share certain attributes that make their adoption very difficult. We propose and program a blockchain-based system that reduces and shares out among the financial institutions (FIs) that work with a customer the costs of the KYC process and also makes it possible for FIs to dynamically update information related to customers and disseminates this information among participating FIs. Additionally, our system addresses some of the attributes that hinder the adoption of previously proposed solutions by FIs. The result is a stand-alone solution that reduces the cost of the KYC process without requiring any central instance to store the customer's data, and in which FIs share the initial costs of the KYC process as well as the running costs of keeping the information about customers up to date.